Catalyzing traffic safety advancements via data linkage: Development of the New Jersey Safety and Health Outcomes (NJ-SHO) data warehouse. (25th November 2019) - Curry, Allison E.; Pfeiffer, Melissa R.; Carey, Meghan E.; Cook, Lawrence J.
Abstract: Objective: Our objective is to describe the development of the New Jersey Safety and Health Outcomes (NJ-SHO) data warehouse, a unique and comprehensive data source that integrates various state-level administrative databases in New Jersey to enable the field of traffic safety to address critical, high-priority research questions. Methods: We have obtained full identifiable data from the following statewide administrative databases for the state of New Jersey: (1) driver licensing database; (2) Administration Office of the Courts data on traffic-related citations; (3) police-reported crash database; (4) birth certificate data; (5) death certificate data; and (6) hospital discharge data as well as (7) childhood electronic records from New Jersey residents who were patients of the Children's Hospital of Philadelphia pediatric health care network and (8) census tract–level indicators. We undertook an iterative process to develop a linkage algorithm in LinkSolv 9.0 software using records for individuals born in select birth years (1987 and 1988) and subsequently execute the linkage for the entire study period (2004–2017). Several metrics were used to evaluate the quality of the linkage process. Results: We identified a total of 62, 685, 619 records and 19, 247, 363 distinct individuals; 10, 352, 998 of these individuals had more than one record brought together during the linkage process. Our evaluation of this linkage suggests that the linkage was of high quality. Conclusions: The resulting NJ-SHO data warehouse will be one of the most comprehensive and rich traffic safety data warehouses to date. The warehouse has already been utilized for numerous studies and will be fully primed to support a host of rigorous studies, both in and beyond the field of traffic safety.